The banking sector and the Swiss financial account during the financial and European debt crises - Raphael A. Auer; Cedric Tille (Aussenwirtschaft, 2016)
The US financial crisis and the later Eurozone crisis have substantially affected capital flows into and out of financial centers like Switzerland. We focus on the pattern of capital flows involving the Swiss banking industry. We first rely on balance-of-payment statistics and show that net banking inflows rose during the acute phases of the crises, albeit with a contrasting pattern. In the wake of the collapse of Lehman Brothers, net inflows were driven by a large retrenchment towards the domestic market by Swiss banks. By contrast, the net inflows from mid-2011 to mid-2012 were driven by large flows into Switzerland by foreign banks. We then use more detailed data from the Swiss banking statistics which allow us to contrast the situation across different banks and currencies. We show that the cycle during the US crisis in bank flows was driven strongly by exposures in US dollars, and to a large extent by Swiss-owned banks. During the Eurozone crisis by contrast, the flight to the Swiss franc and the move away from the Euro was also driven by banks that are located in Switzerland, yet are foreign-owned. In addition, while the demand for the franc was driven by both foreign and domestic customers during mid-2011 to early 2013, domestic demand took a prominent role thereafter.
Keywords: E51; G15; G21; F21; F32; F36; F65; 330; Capital flows; Safe haven; Switzerland; Financial globalization; International banking